Development and Formulation of the Experimental Dentifrice Based on Passiflora mollissima (Tumbo) with and without Fluoride Anion: Antibacterial Activity on Seven Antimicrobial Strains - Frank Mayta-Tovalino; Eloy Gamboa; Richard Sánchez; Jorge Rios; Ramín Medina; Martín García; Jhonn Asencios (International Journal of Dentistry)
Objectives. To develop and formulate a new experimental dentifrice with and without fluoride based on the peel and the fruit of the Passiflora mollissima (tumbo) and also to evaluate its antimicrobial activity against seven bacterial strains. Methods. The sample was calculated using the mean comparison formula, obtaining wells (n = 12) for each of the strains evaluated: S. mutans, E. faecalis, Actinomyces, Lactobacillus, C. albicans, S. sanguinis, and S. oralis. The antibacterial activity of the dentifrice was evaluated by the direct contact technique. Results. It was found that the highest antimicrobial activity was only present in pulp-based dentifrices against strains of S. mutans 21.0 ± 1.8, E. faecalis 16.3 ± 3.9, Actinomyces 22.1 ± 1.3, and Lactobacillus 21.0 ± 1.3. However, in comparison with other strains such as C. albicans, S. sanguinis, and S. oralis, the peel-based dendrifrice of Passiflora mollissima obtained the highest antimicrobial activity. Conclusion. The experimental dentifrice based on Passiflora mollissima had an antibacterial effect against the seven microbial strains during the first 24 and 48 hours.